Media “Cultural Treasure Chest” Bermuatan Multikultural Lokal Lamongan Kelas Iv Siswa Sekolah Dasar - Aryani Nurafifah; Maretha Dellarosa (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
This research is motivated by the low understanding of elementary school students towards the diversity of local cultures around them, this phenomenon is caused by the lack of innovative and contextual learning media. Teachers tend to still use conventional methods, especially in learning cultural diversity. This study aims to develop a Cultural Treasure Chest learning media containing local multicultural Lamongan to improve students' understanding of cultural diversity. The research method used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were fourth grade elementary school students. Data collection techniques used validation questionnaires, user response questionnaires, and learning outcome tests. The results of this study indicate that the developed media obtained a very valid category based on the assessment of media experts and material experts, practical based on teacher and student responses, and effective in terms of improving learning outcomes with the Paired Sample T-Test test results showing a significance value (2-tailed) of 0.000 <0.05 with a calculated t value of -11.637. This indicates a significant difference between the scores before and after media use. The N-Gain calculation of 0.63 is in the moderate category. Therefore, the Cultural Treasure Chest media is suitable for use in learning to improve students' understanding of cultural diversity.